Psychology as technology: industrial psychology for an industrializing China. (3rd July 2022) - Seow, Victor
ABSTRACT: This article examines the advent of industrial psychology in China in the 1930s, asking how it was that this science of work that had been conceived to meet the challenges of industrial society and industrial production came to be taken up in an economy that had, in this period, a small industrial sector. Through this history, which includes a close look at the first industrial psychology study in China, this article shows how workers and workplaces became subjects of systematic study, and the extent and limits of industrial reforms by industrial psychologists who peddled the promise of small changes adding up to large effects.